2008
DOI: 10.1021/jp711396b
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Absorption Maxima of the Photoactive Yellow Protein Resolved via Ab Initio Multiconfigurational Methods

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…We performed a partitioning of the PYP molecule into QM and MM subsystems in a similar fashion to other investigations. [13][14][15][16] However, in variance to 30 previous QM/MM studies, which have used only a fixed point-charge model of the MM surroundings, we describe the environment of the chromophore in a much more detailed way, by considering atom-centered charges, dipoles, and quadrupoles, as well as induced dipoles determined through 35 anisotropic polarizabilities. Both sets of localized properties were calculated for all residues in the protein, using the LoProp approach.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a partitioning of the PYP molecule into QM and MM subsystems in a similar fashion to other investigations. [13][14][15][16] However, in variance to 30 previous QM/MM studies, which have used only a fixed point-charge model of the MM surroundings, we describe the environment of the chromophore in a much more detailed way, by considering atom-centered charges, dipoles, and quadrupoles, as well as induced dipoles determined through 35 anisotropic polarizabilities. Both sets of localized properties were calculated for all residues in the protein, using the LoProp approach.…”
Section: Computational Detailsmentioning
confidence: 99%
“…19 45 This treatment is a significant improvement with respect to earlier theoretical investigations in which only a few of the residues comprising PYP were investigated 10-12 and QM/MM studies describing the MM region with point charges and the QM system semiempirically, where the explicit polarization 50 between the QM and MM system was not taken into account. [13][14][15][16] In fact, it has been shown previously that different point-charge models (e.g. those of the Amber 94 and 03 force field) may give excitation energies that differ by up to 0.6 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Several theoretical studies on PYP have been reported so far [9][10][11]. In these studies, the contribution from neighboring residues was discussed to clarify the protein environmental effect to the spectral shift.…”
Section: Introductionmentioning
confidence: 99%
“…CASSCF wave functions can also (19) be used in the context of second-order perturbation theory (CASPT2), which recovers the dynamic correlation energy and allows for a quantitative prediction of excitation energies. Indeed, in previous work we have shown that CASPT2//CASSCF-based (i.e., CASSCF geometry optimization and CASPT2 energy evaluation) QM/MM calculations reproduce both absorption and emission spectra of proteins incorporating chemically different chromophores (20)(21)(22). For example, such calculations reproduce the λ a max value of Rh with an error of 3 kcal mol −1 only (13).…”
mentioning
confidence: 97%